2020
DOI: 10.3389/fevo.2020.00095
|View full text |Cite
|
Sign up to set email alerts
|

How Do Leaf-Cutting Ants Recognize Antagonistic Microbes in Their Fungal Crops?

Abstract: Leaf-cutting ants employ diverse behavioral strategies for promoting the growth of fungal cultivars in a structure known as fungus garden. As a nutritionally rich resource for the ants, the fungal crop is threatened by microbial antagonists and pathogens. Strategies for protecting the garden against harmful microbes have been described in detail, although the process of microbial threat recognition is not fully understood. Here, we review the literature on leaf-cutting ants' social immunity traits, in search o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 179 publications
(288 reference statements)
0
22
2
9
Order By: Relevance
“…The ants' differential responses to different parasites suggest that the ants can discriminate between different Escovopsis strains as previously suggested (Goes et al, 2020). However, we do not know whether ants' attention to particular morphotypes can be modified by adding or removing other Escovopsis morphotypes or pathogens.…”
Section: The Utilization Of Multifaceted Specific Defense Strategiesmentioning
confidence: 67%
“…The ants' differential responses to different parasites suggest that the ants can discriminate between different Escovopsis strains as previously suggested (Goes et al, 2020). However, we do not know whether ants' attention to particular morphotypes can be modified by adding or removing other Escovopsis morphotypes or pathogens.…”
Section: The Utilization Of Multifaceted Specific Defense Strategiesmentioning
confidence: 67%
“…These tasks involve chemical signals (Schultner and Pulliainen, 2020) processed by the antennal lobes and mushroom bodies, as well as fine motor coordination of the mouthparts, mediated by subesophageal zone circuitry (Paul and Gronenberg, 2002). Minims may deposit pheromones on foraging trails (Howard, 2001;Evison et al, 2008), clean contaminants from incoming leaves and otherwise protect the fungus from microbes (Goes et al, 2020), and defend against parasitic flies (Feener and Moss, 1990).…”
Section: Division Of Labor and Worker Cognitionmentioning
confidence: 99%
“…In leaf‐cutting ants (Hymenoptera: Formicidae: Myrmicinae: Attini; subtribe: Attina), studies demonstrated the wide array of hygienic defenses toward unwelcome microbes that exploit the same resources and niches as their fungal crops (Bonadies et al, 2019 ; Currie et al, 1999 ; Currie & Stuart, 2001 ; Fernández‐Marín et al, 2009 ; Rocha et al, 2014 ; Yek et al, 2012 ) (Figure 1 ). The survival of their fungal cultivars ( Basidiomycota: Agaricales , including Leucoagaricus gongylophorus ) and the microbiota found in the colony (Aylward et al, 2014 ; Barcoto et al, 2020 ; Khadempour et al, 2020 ; Suen et al, 2010 ) relies on a combination of the ants' ability to defend themselves and their partners using cleaning strategies (Goes et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several alien fungi with distinct lifestyles were reported in Atta and Acromyrmex colonies, as generalist mycopathogens (e.g., Trichoderma and Syncephalastrum ), entomopathogens (e.g., Beauveria and Metarhizium , Rodrigues et al, Rodrigues & Pagnocca, 2005 , Rodrigues et al, 2008 ; Goffré & Folgarait, 2018 ), and mycoparasites (i.e., Escovopsis , Currie et al, 2003 ). In theory, if leaf‐cutting ants recognize the diversity of alien fungi entering their colonies, defensive responses are expected to follow their threat levels (Goes et al, 2020 ; Mighell & Van Bael, 2016 ). For instance, increased hygienic responses toward Escovopsis when compared with Trichoderma viride corroborate a possible distinction between mycelium and/or conidia of a specialist and a generalist fungal pathogen, respectively (Currie & Stuart, 2001 ).…”
Section: Introductionmentioning
confidence: 99%